Analysis of Disaster Vulnerability Level and Community Preparedness Index in the Coastal Area of Kupang City in Dealing with Tsunami Disaster - Siwi, Nanda Dewi Pamungkas (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
This study analyzes the vulnerability to disasters and the preparedness index of coastal communities in Kupang City, Indonesia, in facing tsunami risks. Employing a quantitative descriptive method, the research evaluates vulnerability across four categories: physical, social, economic, and environmental. The preparedness index was assessed using variables such as community knowledge, emergency response planning, disaster warning systems, and resource mobilization. The findings reveal that Kelurahan Fatubesi and Oesapa exhibit high vulnerability due to physical and social factors, while other areas demonstrate moderate vulnerability. The overall preparedness index of coastal communities is classified as "nearly ready," with Oesapa Barat and Oesapa showing better preparedness levels compared to other areas. The study emphasizes the need for enhancing disaster awareness, improving infrastructure, and developing community-based risk management strategies to mitigate the impact of tsunamis on coastal populations.